Dipolar Quantum Mixtures of Erbium and Dysprosium Atoms - Trautmann, A.; Ilzhöfer, P.; Durastante, G.; Politi, C.; Sohmen, M.; Mark, M. J.; Ferlaino, F. (Physical review letters, 2018)
We report on the first realization of heteronuclear dipolar quantum mixtures of highly magnetic erbium and dysprosium atoms. With a versatile experimental setup, we demonstrate binary Bose-Einstein condensation in five different Er-Dy isotope combinations, as well as one Er-Dy Bose-Fermi mixture. Finally, we present first studies of the interspecies interaction between the two species for one mixture.